INTEGRATED ELECTROCOAGULATION – MEMBRANE SYSTEM FOR COLOR AND COD REMOVAL OF PALM OIL MILL EFFLUENT: EXPERIMENTAL AND MODELLING - SAAD, MUHAMMAD SYAAMIL (2021)
Palm oil mill effluent (POME) is an oily wastewater generated by palm oil processing mills and alarming growth of palm oil plantation cause massive pollution to the environment and local communities. In this study, electrocoagulation (EC), microfiltration (MF), and a combination of both methods were evaluated on the removal of color as well as chemical oxygen demand (COD) in POME. Parameters studied for EC method were voltage (2 V, 4 V, 6 V, 8 V, 10 V), reaction time (15, 30, 45, 60 minutes) and electrodes. Colour and COD removal exhibit by oxidized iron electrodes shows 94.2% and 69.9% respectively at 10 V and 60 minutes. MF treatment of POME was performed using nylon 6,6 nanofiber membrane (NFM) synthesized via electrospinning technique. From the characterization, the fiber diameter, pore size, and porosity measured were 724.7 nm, 200 nm, and 71.3% respectively and in agreement with the literature for a NFM specification. Removal of color by MF treatment was found to be low (13.5%) but the COD removal was comparable to EC (68.5%) and was justified by the presence of humic and fulvic acid in permeated samples. An Integrated EC-membrane system that operates at low voltage (1 V and 2 V) was proposed to overcome the drawbacks of EC (high energy consumption) and MF standalone (time-consuming). Integrated systems at 2 V manage to remove 51.4% COD and 76.99% color removal which was comparable EC method (4 V and 6 V) and MF standalone. With the best operating condition for EC and integrated EC-membrane system, both treatments were modeled using JMP software and economic evaluation was done to find CAPEX and OPEX. Modeling of EC was found to follow quadratic equation while integrated system follows cubic the best. At an assumption of 75% colour removal, integrated EC-membrane system economical aspect at 2 V (RM2,788,598) outweigh EC at 6 V (RM 3,380,808) and conventional biological treatment (RM 8,468,490) for the span of 15 operating years. Integrated EC-membrane was found feasible to be done on a large scale and more cost-effective than conventional biological method.